Estimating the nucleotide diversity in Ceratodon purpureus (Ditrichaceae) from 218 conserved exon‐primed, intron‐spanning nuclear loci1. (28th March 2013) - McDaniel, Stuart F.; van Baren, Marijke J.; Jones, Kelly S.; Payton, Adam C.; Quatrano, Ralph S.
Abstract : Premise of the study: We developed and tested primers for 218 nuclear loci for studying population genetics, phylogeography, and genome evolution in bryophytes. Methods and Results: We aligned expressed sequence tags (ESTs) from Ceratodon purpureus to the Physcomitrella patens genome sequence, and designed primers that are homologous to conserved exons but span introns in the P. patens genome. We tested these primers on four isolates from New York, USA; Otavalo, Ecuador; and two laboratory isolates from Austria (WT4 and GG1). The median genome‐wide nucleotide diversity was 0.008 substitutions/site, but the range was large (0–0.14), illustrating the among‐locus heterogeneity in the species. Conclusions: These loci provide a valuable resource for finely resolved, genome‐wide population genetic and species‐level phylogenetic analyses of C. purpureus and its relatives.